Case report: Rare Presentation of Intranasal Lobular Capillary Hemangioma - Alberto Taolin (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2025)
Background: Lobular capillary hemangiomas (LCH) are benign acquired vascular lesions of the skin and mucous membranes that predominantly affect the head and neck region. Nasal cavity involvement is very rare and may present with epistaxis and nasal obstruction. Case series: In this case series, we present a case of intranasal LCH. A patient presented with epistaxis and nasal obstruction, and was treated endoscopically. The patient presented with recurrent nosebleeds and nasal obstruction. Surgical excision was performed with no complications observed postoperatively. Discussion: The etiology of LCH is unknown, but certain predisposing factors have been associated with the development of LCH and include trauma. The anterior mucosa of the nasal septum and the tip of the inferior turbinate are the commonly involved sites. Computed tomography scan and histopathology are used to diagnose LCH. Treatment is endoscopic surgical excision. Conclusion: LCH is a rare tumor of the nasal cavity. Treatment of this lesion is surgical with or without preoperative vascular control.